2016
DOI: 10.1177/0193945916670145
|View full text |Cite
|
Sign up to set email alerts
|

APOEε4 and Memory Among Patients With Heart Failure

Abstract: Twenty-three percent to 50% of heart failure (HF) patients have memory loss. Objectives were to (a) characterize major allelic frequency of 2 variants in apolipoprotein ( APOE) gene in HF patients, (b) evaluate differences in memory and serum brain-derived neurotrophic factor (BDNF) levels based on APOE ε4 allele(s), and (c) estimate effect sizes (ESs) and confidence intervals (CIs). In this pilot, 29 HF patients were enrolled and 26 completed. Recall and delayed recall memory were measured at baseline and 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
10
1
Order By: Relevance
“…In previous studies, ε4 frequencies among patients with HF who did not have diagnosis of AD or MCI were 24% and 33%. 19,20 However, in this study, only 14.7% of the HF participants with normal cognition had ε4 allele. Based on the results, it appears that irrespective of their APOE ε4 and ε2 carrier status, participants with HF in this sample were more likely to have AD than those without HF.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In previous studies, ε4 frequencies among patients with HF who did not have diagnosis of AD or MCI were 24% and 33%. 19,20 However, in this study, only 14.7% of the HF participants with normal cognition had ε4 allele. Based on the results, it appears that irrespective of their APOE ε4 and ε2 carrier status, participants with HF in this sample were more likely to have AD than those without HF.…”
Section: Discussioncontrasting
confidence: 62%
“…33 Despite the advances in genomics research related to cognitive dysfunction, two studies have been reported in the HF literature in which the allelic frequencies were studied of APOE ε4 and ε2, and BDNF Val66Met. In a small sample of 29 patients with HF (76% White), 24% had at least one APOE ε4 allele, 19 21% had one APOE ε2 allele, Netherlands, 33% had at least one APOE ε4 allele and having ε4 allele was associated with poorer cognitive function as measured by a neuropsychological battery examining 5 cognitive domains of memory, executive function, visuospatial function, language, and mental speed/attention. 20 In summary, little is known about APOE ε2 and BDNF Met alleles in relation to cognitive dysfunction in HF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Promega BDNF EMax Immunoassay System produces less than 3% cross‐reactivity with other neurotrophic factors and can detect BDNF at concentrations as low as 15.6 pg/ml. The protocol and procedures have been previously published (BDNF Emax ImmunoAssay System, 2009; Pressler et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, Vogels and colleagues 71 reported that 33% of 62 HF patients in the Netherlands had at least one copy of the APOE-ε4 allele. In the preliminary MEMOIR-2 study, 7 (24.1%) of 29 HF patients had APOE-ε4 allele, 73 potentially increasing their risk for memory disorders and altering their responses to cognitive training interventions.…”
Section: Methodsmentioning
confidence: 99%